Familial neonatal atrial tachycardia. - Balaji, S. (1996)
A father and his two sons each presented with atrial tachycardia in the newborn period. The father went on to develop dilated cardiomyopathy. The first son (who also had transposition of the great arteries) died from the arrhythmia after surgery. The second son is currently successfully managed pharmacologically.